06.10 Effects of resveratrol and a resveratrol-salicylate hybrid molecule on activation of human cd4+ t- cells. (1st March 2017) - Goldhahn, Katrin; Kloesch, Burkhard; Aldawsari, Farid; Velazques-Martinez, Carlos; Schmetterer, Klaus; Steiner, Guenter
Abstract : Background: Aberrant T-cell responses are crucially involved in the pathogenesis of systemic autoimmune diseases such as rheumatoid arthritis (RA) leading to chronic inflammation and organ damage. Consequently, substances modulating T-cell activation may have therapeutic benefit in RA and related rheumatic diseases. Resveratrol is a natural occuring polyphenol mainly produced in plants. The beneficial effects of resveratrol are due to its anti-inflammatory, anti-carcinogenic and anti-oxidant activities. The aim of this study was to compare the effects of resveratrol and a novel resveratrol-salicylate hybrid molecule (C10) on human CD4 + T-cells. Methods: CD4 + T-cells were isolated from healthy donors and pre-incubated with different concentrations of resveratrol or C-10 before being stimulated with anti-CD3/anti-CD28 antibodies. After 24 hour and 72 hour, respectively, cell culture supernatants were harvested and IL-2, IFN-γ and TNF-α release were quantified by ELISA. Proliferation rate was measured by thymidine incorporation. In addition, the up-regulation of the early activation markers CD25, CD69, CD71 and CD98 was analysed and phosphorylation of the MAP-kinase ERK as well as AKT and SRP6 was determined by western blot or flow cytometry. Results: Inhibition of IL-2, IFN-γ and TNF-α release was significantly more effective when the cells were treated with C-10 as compared to resveratrol. Thus, a decrease of cytokine expression was observed already at 6.25 µM C-10 whereas resveratrol inhibited cytokine production only at 25 µM or 50 µM significantly. Moreover, the proliferation rate was significantly more decreased in the presence of C-10. The expression of CD25, CD69, CD71 and CD98hc was reduced to a similar degree by both compounds. Furthermore, phosphorylation of ERK, Akt and S6RP was attenuated when the cells were incubated with resveratrol or C-10. Conclusion: Our data demonstrate that C-10 suppressed cytokine secretion and proliferation more effectively than resveratrol. Both compounds influence the phosphorylation of important signalling molecules. Thus, the resveratrol-salicylate hybrid molecule C-10 significantly amplified the effects of resveratrol in CD4 + T- cells and might be used in the future for treatment of RA and other T-cell driven autoimmune diseases.